Cálculo e implementação do índice de Desenvolvimento da Gestão Municipal (IDGM) no município de Itabaiana/Se - Jorge, Marco Antonio; Frei, Fernando [UNESP]; Sales, John Max Santos; Lima, Brenda Machado (My University, 2010)
The scarcity of resources which frequently confronts the State, coupled with demands to provide assistance to a needy population, requires that public administrators formulate efficient and effective policies to pursue its goals. It is fundamental that such policies are based on solid information of existing conditions. As such, the availability of reliable and updated socio-economic indicators is an important tool on which to fundament public policies. The present paper aims to present a Municipal Development Index – Municipal Management Development Index (IDGM) – calculated for the city of Itabaiana/SE, and is divided in two sections. The first discusses the concept of economic development and the evolution of measurement frameworks, with emphasis on the IHD and some of its limitations. The second section describes an estimated IDGM for the city of Itabaiana, as well as its methodology, results, and a brief comparative analysis with four municipalities from the state of São Paulo. Itabaiana’s IDGM reached 849 points (the maximum is 1.000), which infers a good developmental condition.

A escassez de recursos com que frequentemente se defronta o setor público, somada à necessidade de atendimento às carências da população, exige dos gestores a formulação de políticas eficazes e eficientes no alcance de seus objetivos. É fundamental que tais políticas estejam alicerçadas em informações sólidas acerca da realidade. Assim, a disponibilidade de indicadores socioeconômicos confiáveis e atualizados é um importante instrumento para balizar as políticas públicas. O artigo tem por objetivo apresentar o Índice de Desenvolvimento da Gestão Municipal (IDGM), calculado para o município de Itabaiana/SE, e está estruturado em duas seções. Na primeira, discutem-se o conceito de desenvolvimento econômico e a evolução em sua forma de mensuração, com destaque para o Indíce de Desenvolvimento Humano (IDH) e algumas de suas limitações. Na segunda seção descreve-se o IDGM estimado para o município de Itabaiana, bem como sua metodologia, resultados e uma breve análise comparativa com o IDM de quatro municípios paulistas. O IDGM de Itabaiana atingiu 849 pontos (em mil possíveis), o que coloca o município sergipano em boas condições de desenvolvimento.
Keywords: Local Development; Indicator; Itabaiana/SE; Desenvolvimento Local; Indicador; Itabaiana/SE